Efektifitas Teknik Relaksasi Nafas Dalam Terhadap Penurunan Nyeri Akut Pada Pasien Pasca Operasi Apendiktomi Di Rumah Sakit PKU Muhammadiyah Temanggung - Sutri Ardy Ramadhan; Tri Suraning Wulandari; Ratna Kurniawati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Jenderal Achmad Yani Yogyakarta, 2025)
Background: Appendectomy is a surgical procedure to treat appendicitis, but postoperative pain is a common complication. If left unmanaged, pain can affect sleep, delay healing, increase sympathetic activity, and cause emotional distress. Non-pharmacological methods such as deep breathing relaxation are safe and effective options to manage this pain. Deep breath relaxation techniques have been shown to effectively reduce pain intensity by relaxing muscle spasm, which is caused by an increase in prostaglandins, leading to vasodilation and increased blood flow to areas of spasm and ischemia. In addition, this technique can stimulate the release of endogenous opioids, such as enkephalins and endorphins. Enkephalins function as neurotransmitters that regulate pain, emotions and stress, while endorphins provide a sense of relaxation, comfort and calmness to the body. According to WHO (World Health Organization) in 2022, the number of deaths due to appendicitis reached 21,000 clients with the number of male sufferers being higher than female. Purpose: This study aimed to determine the effectiveness of deep breathing relaxation techniques in reducing acute pain in post-appendectomy patients. Methods: This was a qualitative case study involving two postoperative patients. Data were collected through observation, interviews, and pain scale assessments using the Numeric Rating Scale (NRS), before and after applying deep breathing techniques for 3 days (twice daily for 10–15 minutes). Results: Both patients showed a decrease in pain levels, with improved indicators such as reduced grimacing, restlessness, and normalized vital signs. Conclusion: Deep breathing relaxation techniques are effective in lowering acute pain levels in appendectomy patients and can be used as supportive nursing care alongside pharmacological treatment.